A learning management system adoption framework for higher education: the case of Iraq - Radif, Mustafa (Cranfield University, 2016)
This study focuses on the implementation of Learning Management System (LMS) in the higher education sector in Iraq. Its aim is to develop a policy adoption framework for LMS implementation by scientifically investigating LMS adoption using a model that combines the principles of the Technology Acceptance Model (TAM) and Technology-Organisation-Environment (TOE) framework. The research methodology comprises of seven stages that adopts the interpretive paradigm and a mixed-methods research design. A case study design is used to investigate LMS integration in the University of Al-Qadisiyah. A TAM-TOE questionnaire is developed for the academic staff of the University of Al-Qadisiyah, in which the perceived usefulness and perceived ease of use of LMS are analysed in the case organisation. The technological, organisational, and environmental aspects of LMS implementation are also examined. The survey received valid responses from 283 academic staff. In-depth semi-structured interviews of 8 academics, administrative staff and IT personnel contributed to the qualitative data. The survey respondents are selected using stratified sampling whilst purposive sampling is used to select the interview participants. The questionnaire data was analysed using correlation analysis, whilst thematic analysis is used for the interview data. The study identifies the barriers to LMS implementation as: Lack of or limited teachers’ training, lack of commitment to constructivist pedagogy, lack of experience to use the new technology, lack of technical support, and lack of appropriate educational software. These results feed into the policy framework design. The contribution to research knowledge includes the creation of a new adoption model derived from TAM and TOE to examine the LMS implementation barriers in a war recovering economy like Iraq. This approach the integration of academic users’ acceptance with macro-level factors like government support. The results lease to the development of the LMS policy framework to guide policy makers to prioritise their limited LMS investments. The novelty of the work is the bringing together the considerations of the individual users and the socio-economic context.
Keywords: TAM model; TOE model; TPB model; Critical factor; Government support; Technology acceptance; Policy framework; Perceived ease of use; Perceived usefulness; Intention to use; Readiness; Willingness to use